2022
DOI: 10.1038/s42004-022-00732-1
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of aminophenols in forming nitrogen-containing brown carbon from iron-catalyzed reactions

Abstract: Nitrogen-containing organic carbon (NOC) in atmospheric particles is an important class of brown carbon (BrC). Redox active NOC like aminophenols received little attention in their ability to form BrC. Here we show that iron can catalyze dark oxidative oligomerization of o- and p-aminophenols under simulated aerosol and cloud conditions (pH 1–7, and ionic strength 0.01–1 M). Homogeneous aqueous phase reactions were conducted using soluble Fe(III), where particle growth/agglomeration were monitored using dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…38,64,65 Although triones in ambient aerosols were less reported, 66 they have been suggested as possible contributors to BrC generated from aqueous-phase reactions. 67,68 The collective evidence demonstrates that carbonyl chromophores are ubiquitous constituents of SOA and may play an active role in secondary BrC formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…38,64,65 Although triones in ambient aerosols were less reported, 66 they have been suggested as possible contributors to BrC generated from aqueous-phase reactions. 67,68 The collective evidence demonstrates that carbonyl chromophores are ubiquitous constituents of SOA and may play an active role in secondary BrC formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There remain unresolved research questions on the role of metals in aqueous and multiphase transformations of NOC and formation of secondary light-absorbing NOC. In the following section, recent studies on the reactivity of soluble and insoluble Fe with phenolic chemical compounds, o - and p -aminophenols ( o AP and p AP) 49 and gallic acid, 50 are presented.…”
Section: Noc Production From Homogeneous and Heterogeneous Fe-catalyz...mentioning
confidence: 99%
“…The net redox potential values () for the reactions between phenol or aniline and Fe( iii ) are negative indicating non-spontaneity under acidic conditions, whereas they are positive between o AP and p AP. In our studies using o AP and p AP 49 conducted at room temperature (296 K), we used soluble Fe( iii ) and insoluble Fe from AZTD to catalyze redox chemistry and analyze soluble and insoluble reaction products for comparison with those obtained from metal free oxidation of o AP and p AP that yields polymeric products referred to as poly( o -aminophenol) and poly( p -aminophenol). 70 We found that soluble Fe( iii ) can catalyze dark oxidative oligomerization of o AP and p AP under simulated aerosol and cloud conditions (pH 1–7) and ionic strength 0.01–1 M adjusted by ammonium sulfate.…”
Section: Noc Production From Homogeneous and Heterogeneous Fe-catalyz...mentioning
confidence: 99%
See 1 more Smart Citation
“…2,[19][20][21][22][23] Previous laboratory studies have shown that Fe(III) can catalyze oligomerization reactions with known constituents of BBOA and industrial emissions to produce lower volatility secondary brown carbon (BrC) products. [24][25][26][27][28][29][30][31] Reaction solutions were open to air and dissolved O 2 acted as an oxidant. These irreversible, oxidative polymerization reactions formed waterinsoluble, black particles in acidic systems (pH 3) with excess Fe(III).…”
Section: Introductionmentioning
confidence: 99%